Aligning Recovery and Legal Certainty in Restorative Justice for Theft Offenses - Faizal Tri Noviyanto; Hanuring Ayu Ardhani Putri; Suparwi Suparwi (Jurnal Ilmu Hukum Kyadiren, 2026)
The paradigm shift in Indonesian criminal law following the enactment of Law Number 1 of 2023 on the Criminal Code has strengthened the restorative justice approach in resolving theft offenses by emphasizing restoration rather than punishment. This study aims to analyze legal protection and legal certainty in the implementation of restorative justice for theft offenses under the new Criminal Code. The research employed a normative juridical method using statutory, conceptual, and case approaches and was analyzed qualitatively. The findings indicate that restorative justice provides more comprehensive protection for victims, offenders, and society through compensation for losses, offender accountability, and the restoration of social relationships. Nevertheless, legal certainty continues to face challenges arising from regulatory fragmentation and differing interpretations among law enforcement authorities. This study concludes that regulatory harmonization and the strengthening of implementation mechanisms are essential to achieving a fair, humane, and restorative criminal justice system.